Pengaruh Endorser Credibility dan Brand Credibility Terhadap Purchase Intention yang Dimediasi oleh Attitude Towards Brand pada Produk Y.O.U di Sumatera Barat - Nismala Roza; Gesit Thabrani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the influence of endorser credibility and brand credibility on purchase intention which is mediated by attitude towards brand on Y.O.U beauty products in West Sumatra. This study uses quantitative methods by collecting data through questionnaires involving 200 respondents. Data analysis was carried out using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with SmartPLS v.4.0.9.9 software. The research results show that endorser credibility and brand credibility have a positive and significant effect on attitude towards brand. Apart from that, attitude towards brand also has a positive influence on purchase intention. Furthermore, attitude towards brand is proven to mediate the relationship between endorser credibility and purchase intention as well as brand credibility and purchase intention. The implications of this research can be used by cosmetic companies in designing more effective marketing strategies by considering the selection of credible endorsers and increasing brand credibility in order to increase consumer purchase intention.